'The wish to paint': Bowen and the Visual Arts. Issue 1 (May 2021) - Waldron, Michael
Abstract : Throughout her life, Elizabeth Bowen maintained a rich network of artist friends and acquaintances. She often attended exhibitions and was an astute, sometimes caustic critic in letters as well as reviews. Her short tenure as an art student is an often mentioned but rarely, if ever, explored biographical fact, yet it was a key moment in her creative development. It is perhaps unsurprising then that she began to write while 'still under the influence of … the wish to paint.' This essay considers Bowen's significant relationship with the visual arts, from her art training and networks to her critical engagement and deeply visual prose. In childhood, Bowen was taught to paint by Elizabeth Yeats and forged a lasting friendship with Mainie Jellett, one of Ireland's great modernists. In 1918, Bowen enrolled at the LCC Central School of Arts and Crafts but, convinced she lacked the requisite artistic talent, she withdrew from her studies after only two terms. This sense of failure plunged her into an artistic crisis from which writing offered a creative way forward. Tellingly, Bowen later reflected that her earliest stories 'had the character of a last hope'. In describing the best of her writing as 'verbal painting', Bowen offers us a lens through which to conceptualise the dynamic dialogue between her more experimental prose and visual modernism. Drawing together aspects of her artistic formation, milieu, and taste, this essay ultimately seeks to provide a series of layered contexts to enrich our understanding of Bowen's fictions, including The Last September (1929) and To the North (1932).